Catalytic Asymmetric Substitution Reaction of 3-Substituted 2-Indolylmethanols with 2-Naphthols - Lan, Jin-Ping; Lu, Yi-Nan; Chen, Ke-Wei; Jiang, Fei; Gao, Feng; Zhang, Yu-Chen; Shi, Feng (Synthesis, 2020)
A catalytic asymmetric substitution of 3-substituted 2-indolylmethanols with 2-naphthols has been established under the catalysis of chiral phosphoric acid. By this approach, a series of structurally diversified triarylmethane derivatives were obtained in moderate to high yields with good enantioselectivities (up to 97% yield, 95:5 er). This approach not only enriches the chemistry of 2-indolylmethanol-inolved catalytic asymmetric substitutions, but also provides a useful method for the enantioselective synthesis of chiral triarylmethane derivatives.
Keywords: indolylmethanol; 2-naphthol; substitution; chiral phosphoric acid; enantioselectivity